A conceptual model on cloud computing and SME performance: Resource-Based View - Salleh, Noor Afzan; Hussin, Husnayati (IEEE, 2016)
Despite the promising future of cloud computing to be successfully adopted for SMEs’s daily operations, researchers, policy makers and SME owners are still grappling with how effective cloud computing could be customized to monitor respective SME performances. The literature review revealed that there is still a lack of research on the post-adoption of cloud computing, particularly concerning the key variables and interrelationships which are mostly divergent and that produce varied results. Therefore, the main purpose of this paper is to develop an integrative cloud computing model underpinned by the Resources-Based View Theory (RBV) and also via applying the concept of IT business value. This study seeks to bridge the knowledge gap of cloud computing complementary organizational capabilities identified as the internal factor. As future research guidelines, this research will fill the theoretical gap especially concerning the impacts of cloud computing among Malaysian SME adopters.